Level of Student Satisfaction with the Performance of Electrochemical Analysis Practice Instructors - Moh Hayat; Arif Muchyidin; Udin Asrorudin (Journal of General Education and Humanities, 2025)
This study aims to analyze student satisfaction with instructors' performance in Electrochemical Analysis Practice at AKA Bogor Polytechnic. This study uses a quantitative approach with a survey method. Data was collected through a questionnaire based on the Likert scale, which was distributed to 23 students who had completed the course. Data analysis is carried out descriptively with frequency and percentage calculations, then converted into qualitative information. The study results showed that the overall level of student satisfaction was in the "good" category, with an average of 72.24%. The aspect of professionalism obtained the highest score (73.62%), while the aspect of practice implementation had the lowest score (69.56%). These results show that even though students are satisfied, there is room for improvement, especially in implementing practice. The main recommendations are developing technology-based teaching materials, improving laboratory equipment, and providing more comprehensive practical tutorials. This finding is expected to improve the quality of electrochemistry practicum learning.